2012
DOI: 10.1589/jpts.24.901
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feasibility of Interactive Commercial Nintendo Gaming for Chronic Stroke Rehabilitation

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the effect of interactive games played on a Nintendo Wii on postural control, motor function and functional independence of chronic stroke patients. [Subjects and Methods] Twenty chronic stroke patients were recruited for this study. The subjects were randomly divided into experimental and control groups. The experimental group played interactive games using the Nintendo Wii for 30 minutes a day, 3 times a week, for 3 weeks, whereas the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 11 publications
0
42
0
8
Order By: Relevance
“…11,14 However, in the study of Barcala et al 14 both groups after intervention showed a significant improvement after use of Wii Fit games (platform, fish, and rope).…”
Section: Functional Independencementioning
confidence: 89%
See 2 more Smart Citations
“…11,14 However, in the study of Barcala et al 14 both groups after intervention showed a significant improvement after use of Wii Fit games (platform, fish, and rope).…”
Section: Functional Independencementioning
confidence: 89%
“…In this line, Kim et al 11 concluded that NW appears to be an effective intervention to improve motor function in poststroke chronic patients, as they observed a significant improvement (P ,.05) in the Modified Motor Assessment Scale after 3 weeks of treatment with the Wii Sports' games (tennis and boxing) in the experimental group (34.70 6 6.20) compared to controls (33.57 6 1:51).…”
Section: Motor Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, minor side effects were reported: 3 participants complained of increased spasticity 25 and some participants appeared to be at risk of losing balance, as they were too engrossed with the games. 25 The authors recommended that ample supervision should be provided when using Wii as an intervention for patients with stroke. 25 …”
Section: Attrition and Safetymentioning
confidence: 99%
“…25 The authors recommended that ample supervision should be provided when using Wii as an intervention for patients with stroke. 25 …”
Section: Attrition and Safetymentioning
confidence: 99%